«Saup ben trovar e cantar»: oralità e performance tra lirica d'Oc e del Sì (Mantichora. Italian Journal of Performance Studies, 2020)
This article analyses the oral and performative aspects of medieval lyric poetry in Languedoc and Italy. First, it investigates the contacts between the troubadours with their “secular” performance and the Church with its liturgical and paraliturgical repertoire, intended as a particular form of “sacred” performance. Then, the article dwells upon the contacts of the trobadoric lyric poetry with the ritual of the feudal courts, which constituted a cultural and social coté and a milieu of ideological solidarity between the poets and their public. Finally, it focuses on the relationships between poetry and music in medieval lyric and explains their development between Occitan and Italian lyric.